ANALISIS INTERPRETASI MAKNA PESAN MORAL DALAM FILM NGERI – NGERI SEDAP - Ryandi, Dwi; Abidin, Sholihul (LPPM Universitas Putera Batam, 2024)
In this modern age of globalization, there are many alternatives or media for us and the international community to convey messages and communications, such as telephones, letter messages, and others. The development of the internet, we can access whatever we want in cyberspace, for example is movies. Film is one of the information media that contains fictional or non-fictional stories that are long and entertainment or entertaining. Movies began to flourish in the 20th century and experienced their peak in 2010 and above. Film is not only intended for commercial or entertainment purposes, but the film has the purpose of conveying an important implied message that can only be understood by people who observe it deeply and carefully. In the world of cinema it is called Easter Egg. In the world of Communication Science studies, Easter Egg is called Semiotics, which is the study of signs. Semiotics is a science that studies signs in the world of communication, one of which is used to observe the implied message contained in the film. One of the films that has a good and interesting implied message to be examined is the film that researchers will observe is